Interactions between planets and evolved stars - Shengbang, Q. (2016)
Searching for planetary companions to evolved stars (e.g., white dwarfs (WD) and Cataclysmic Variables (CV)) can provide insight into the interaction between planets and evolved stars as well as on the ultimate fate of planets. We have monitored decades of CVs and their progenitors including some detached WD binaries since 2006 to search for planets orbiting these systems. In the present paper, we will show some observational results of circumbinary planets in orbits around CVs and their progenitors. Some of our findings include planets with the shortest distance to the central evolved binaries and a few multiple planetary systems orbiting binary stars. Finally, by comparing the observational properties of planetary companions to single WDs and WD binaries, the interaction between planets and evolved stars and the ultimate fate of planets are discussed.